Sport sites in ancient anatolia : stadiums - ÇOTUK, MÜFİDE (My University, 2004)
Today we have much evidence that modern Sports Culture has its roots in Ancient Olympic Games. Many excavations are held by archaeologists to understand the idea of sport as the ancient world's culture by searching Ancient Olympia. However there are many ancient stadiums and maybe many more are waiting to come into daylight all over the world, where the ancient civilizations breathed. It is clear that promotion and protection of these sport sites can help us to understand sport culture in civilizations other than Ancient Olympia and help us to see the connections between those that continue to this day.